Contemporary Issues in Biomedical Ethics: Principles, Conflicts, and Emerging Challenges in Modern Healthcare - Ahmed A. Alansary; Shams S. Alsaad (American Journal of Biomedicine and Pharmacy, 2026)
Biomedical ethics has become an operational core of modern healthcare, shaping clinical decisions, biomedical research governance, and policy-making under conditions of technological acceleration and resource constraint. Although the principles of autonomy, beneficence, non-maleficence, and justice remain the dominant analytic framework in applied ethics, contemporary dilemmas increasingly originate from system-level forces such as algorithmic decision support, large-scale health data reuse, and global inequities in access to care. This review synthesizes current debates across clinical ethics, research ethics, AI ethics, and digital health governance, emphasizing (i) the persistent conflict between individual rights and population-level benefit, (ii) bias and accountability challenges in AI systems, (iii) evolving consent models for data-intensive research, and (iv) distributive justice tensions in scarce-resource contexts. Strengthening ethical literacy and adaptive governance frameworks is essential to preserve trust, equity, and scientific integrity in contemporary healthcare.